PENGURANGAN NYERI MENSTRUASI: PENDAMPINGAN TERAPI PIJAT SHIATSU DAN ABDOMINAL STRETCHING EXERCISE - Roni Rowawi; Lina Herlina (Jurnal Widya Laksmi: Jurnal Pengabdian Kepada Masyarakat, 2025)
Menstrual pain (dysmenorrhea) is a common complaint among adolescent girls and can interfere with learning activities as well as daily quality of life. So far, the management of menstrual pain has mostly relied on medication, even though there are safe non-drug methods that can be practiced independently, such as shiatsu massage therapy and abdominal stretching exercise. This community service activity aimed to assist students in learning and practicing these two techniques as an effort to reduce menstrual pain. The program was carried out at SMK 5 Karawang through education, demonstrations, and group practice. Participants received a brief explanation about menstrual pain, followed by hands-on guidance to directly try shiatsu massage and abdominal stretching movements. The mentoring process was interactive, including discussions and Q&A sessions, and participants were provided with a simple guidebook so they could continue practicing at home. The results showed an improvement in students’ knowledge and skills based on pre- and post-activity evaluations. Most participants were able to perform the techniques correctly, and many reported a reduction in menstrual pain after practicing the exercises. A simple analysis comparing pre-test and post-test results indicated a clear positive difference. In conclusion, mentoring on shiatsu massage and abdominal stretching exercise can be an easy, safe, and beneficial non-drug solution for adolescent girls in reducing menstrual pain. This program also raised students’ awareness of the importance of reproductive health from an early age.